Assessing the impact of flexible work arrangements on employee job satisfaction in Malaysia - Liu Shuo; Kharmeyni Jumbulingam; Hossam Fadel; Caren Angellina Mimaki (Review of Management, Accounting, and Business Studies, 2022)
This study highlighted the implications of a flexible work structure in improving job satisfaction in the country of Malaysia. Demographic analysis, validity, normality, reliability, and multiple regressions were performed to understand the connection between the research variables such as the flexibility of work arrangements, increment and appraisal, organizational environment, work pressures, and job satisfaction. Four hypothetical statements were formed based on the independent and dependent variables of the study. H1 and H2 were not supported; on the other hand, H3 and H4 were supported, as the significant value was more than 0.05. A total of 103 participants or 68.7% of respondents were female, while 31.3% were male. Cronbach’s Alpha value was taken into consideration in terms of conducting the reliability test, and it was analysed that the variables were reliable. Biased attitudes and news were found while generating the findings, created due to the poor performance of the responses. The research found that Malaysian participants did not believe in the factors that job satisfaction is increased due to appraisals, and the flexibility of work arrangements is not that important as the variables are not supported. The research generated the finding that a positive work culture and work environment enhance the efficiency of the workers by increasing job satisfaction among them. The employees considered that work pressure needed to be possessed by the employees to get job satisfaction.